Dumbbell-shaped dermoid cyst of the orbit: Case report - Ouassime Kerdoud; Rachid Aloua; Ousmane Belem; Zahra Hmoura; Faiçal Slimani (Elsevier, 2021)
Introduction: Dermoid cysts are developmental choristomas (an abnormal arrangement of tissues not normally present at the site) and are oftenevident soon after birth.The incidence of orbital dermoid cysts is generally reported to be 3%-9% of all orbital tumors; Orbital dermoid cyst is a rare cause of orbital tumor in the adult population. Case report: The authors report the case of a 35-year-old man who presented with a mass in the left upper eyelid, evolving since birth, associated with exophthalmos and ptosis. Orbital CT confirmed the presence of two fatty formations, one intra-orbital and one extra-orbital, which communicate with each other through a bony canal in the outer wall of the left orbit. The diagnosis of an orbital dermoid cyst could be establishedThe patient underwent a lateral orbitotomy that allowed resection of this dumbbell-shaped tumor extending intraorbital. Discussion: Orbital dermoid cyst is a rare cause of orbital tumor in the adult population. They are divided into deep and superficial lesions. Superficial dermoids are noticed during the first years of life, but those that are located more deeply do not become clinically evident until the subject is 15-40 years of age (Scofield-Kaplan et al., Dec. 2018) [4]. They frequently occur near the orbital rim, but may occur in the deeper intraorbital components where the two lobes of the cyst are connected by a bony canal (dumbbell-shaped dermoid).Although dermoid cysts are benign, most of them are removed surgically because the patient presents with a cosmetically visible lesion or ocular symptoms caused by the cyst. Conclusion: Management of dermoid cysts requires complete excision although it is complicated because of the compressive effects of the deep component.